La inmunidad de ejecución de los Estados en la Convención de Naciones Unidas sobre las inmunidades jurisdiccionales de los Estados y de sus bienes (Revista Española de Derecho Internacional, 2006)
This paper analyses the provisions included in the United Nations Convention on Jurisdictional Immunities of States and their Properties relating to the enforcement immunity of States, a text that was adopted in December 2004 by the UN General Assembly. The article shows the need to have a convention of these characteristics but also the doubts generated by its contents, since it puts individuals in a difficult position, as far as the protection of their interests is concerned, in those cases where they seek the enforcement of a sentence against the goods of a foreign state.